A novel hydrogel-based treatment for complete transection spinal cord injury repair is driven by microglia/macrophages repopulation. (April 2020) - Ma, Dezun; Zhao, Yannan; Huang, Lei; Xiao, Zhifeng; Chen, Bing; Shi, Ya; Shen, He; Dai, Jianwu
Abstract: Microglia/macrophage mediated-inflammation, a main contributor to the microenvironment after spinal cord injury (SCI), persists for a long period of time and affects SCI repair. However, the effects of microglia/macrophage mediated-inflammation on neurogenic differentiation of endogenous neural stem/progenitor cells (NSPCs) are not well understood. In this study, to attenuate activated microglia/macrophage mediated-inflammation in the spinal cord of complete transection SCI mice, a combination of photo-crosslinked hydrogel transplantation and CSF1R inhibitor (PLX3397) treatment was used to replace the prolonged, activated microglia/macrophages via cell depletion and repopulation. This combined treatment in SCI mice produced a significant reduction in CD68-positive reactive microglia/macrophages and mRNA levels of pro-inflammatory factors, and a substantial increase in the number of Tuj1-positive neurons in the lesion area compared with single treatment methods. Moreover, most of the newborn Tuj1-positive neurons were confirmed to be generated from endogenous NSPCs using a genetic fate mapping mouse line (Nestin-CreERT2; LSL-tdTomato) that can label and trace NSPC marker-nestin expressing cells and their progenies. Collectively, our findings show that the combined treatment method for inhibiting microglia/macrophage mediated-inflammation promotes endogenous NSPC neurogenesis and improves functional recovery, which provides a promising therapeutic strategy for complete transection SCI.